Characterization of spent nickel–metal hydride batteries and a preliminary economic evaluation of the recovery processes. (3rd March 2016) - Lin, Sheng-Lun; Huang, Kuo-Lin; Wang, I-Ching; Chou, I-Cheng; Kuo, Yi-Ming; Hung, Chung-Hsien; Lin, Chitsan
Abstract: Valuable metal materials can be recovered from spent nickel–metal hydride (NiMH) batteries. However, little attention has been paid to the metal compositions of individual components of NiMH batteries, although this is important for the selection of the appropriate recycling process. In this study, NiMH batteries were manually disassembled to identify the components and to characterize the metals in each of these. A preliminary economic analysis was also conducted to evaluate the recovery of valuable metals from spent NiMH batteries using thermal melting versus simple mechanical separation. The results of this study show that metallic components account for more than 60% of battery weight. The contents of Ni, Fe, Co, and rare earth elements (REEs) (i.e., valuable metals of interest for recovery) in a single battery were 17.9%, 15.4%, 4.41%, and 17.3%, respectively. Most of the Fe was in the battery components of the steel cathode collector, cathode cap, and anode metal grid, while Ni (>90%) and Co (>90%) were mainly in the electrode active materials (anode and cathode metal powders). About 1.88 g of REEs (Ce, La, and Y) could be obtained from one spent NiMH battery. The estimated profits from recovering valuable metals from spent NiMH batteries by using thermal melting and mechanical processes are 2, 329 and 2, 531 USD/ton, respectively, when including a subsidy of 1, 710 USD/ton. The findings of this study are very useful for further research related to technical and economic evaluations of the recovery of valuable metals from spent NiMH batteries. Implications : The spent nickel–metal hydride (NiMH) batteries were manually disassembled and their components were identified. The metals account for more than 60% of battery weight, when Ni, Fe, Co, and rare earth elements (REEs) were 17.9%, 15.4%, 4.41%, and 17.3%, respectively, in a single battery. The estimated profits of recovering valuable metals from NiMH batteries by using thermal melting and mechanical processing are 2, 329 and 2, 531 USD/ton, respectively, when including a subsidy of 1, 710 USD/ton. These findings are very useful to develop or select the recovery methods of valuable metals from spent NiMH batteries.